Reduced stratum corneum acylceramides in autosomal recessive congenital ichthyosis with a NIPAL4 mutation. Issue 1 (January 2020) - Murase, Yuya; Takeichi, Takuya; Kawamoto, Akane; Tanahashi, Kana; Okuno, Yusuke; Takama, Hiroyuki; Shimizu, Eri; Ishikawa, Junko; Ogi, Tomoo; Akiyama, Masashi
Highlights: A novel frameshift mutation in NIPAL4 was identified in an ichthyosis patient. Expression of IL-17/TNFα-related genes was upregulated in the ichthyotic skin. Major acylceramides were reduced in the patient's stratum corneum. Stratum corneum acylceramide amounts were partly restored after retinoid treatment. Abstract: Background: NIPAL4, encoding the NIPA-like domain containing 4 protein (NIPAL4), is one of the causative genes of autosomal recessive congenital ichthyosis (ARCI). The physiological role of NIPAL4 and the pathogenetic mechanisms of ARCI caused by NIPAL4 mutations remain unclear. Objective: To clarify the changes of ceramide components in the lesional stratum corneum (SC) and the gene expression profile in the lesional skin of an ARCI patient with a novel frameshift mutation in NIPAL4 . Methods: We performed ultrastructural and immunohistochemical analyses of the skin. We used RNA sequencing to determine the mRNA expression in the skin of the patient and healthy individuals. We investigated ceramide components using tape stripped SC samples from the patient. Results: mRNA expression profiling in the patient's skin showed significant upregulation of IL-17/TNFα-related genes ( IL17C, IL36A, IL36G, S100A7A, S100A9 ) and psoriasis hallmark genes ( VNN3, LCE3D, PLA2G4D ), and significant downregulation of lipid-associated genes ( GAL, HAO2, FABP7 ). Ceramide analysis in the patient's SC revealed amounts of CER[NS] with carbon chain-length (C) 32–52 were increased, while amounts of most acylceramide with C66:2 - C72:2 were reduced relatively to those in healthy individuals. After the retinoid treatment, CER[NS] with carbon chains C46–54, CER[EOH] and CER[EOP] increased. Conclusion: IL-17C and IL-36 family cytokines might be involved in the pathogenetic process of ARCI with NIPAL4 mutations. Reduced amounts of the acylceramides in the SC are associated with the skin phenotype due to NIPAL4 mutations. Efficacy of the oral retinoid treatment might be due to restored amounts of CER[EOH] and CER[EOP] in the SC.